India's population : aspects of quality and control - Mitra, Asok, 1917-; Family Planning Foundation (India); Indian Council of Social Science Research (New Delhi : Abhinav Publications, 1978)
Study on the implications of population growth and problems likely to arise if the present rate of population growth is not controlled.
'A Family Planning Foundation/ICSSR book.'
Includes index.
Bibliography : v. 2, pages [877]-916.
Keywords: Labor supply -- India; India -- Population; India -- Social conditions -- 1947-